Tsarist Doctors in the Implementation of Peter the Great’s Foreign Policy Initiatives in 1716–1721 - A. V. Morokhin (Vestnik MGIMO-Universiteta)
The article is devoted to the role of tsarist doctors in solving several foreign policy issues in Russia during the reign of Peter the Great. It analyzes the activities of two doctors Robert Areskin and George Polikala. Areskin played a crucial role in Peter I 's communication with the Jacobites under deteriorating relations between Russia and England in 1717-1718. Polikala, in turn, assisted the Russian government in several interactions with the Ottoman Empire.Sources indicate that R. Areskin was the leading lobbyist for the idea of the Russian government supporting James III Stuart. With the help of his relatives, who actively supported the overthrown dynasty, Areskin negotiated with representatives of the Swedish King Charles XII and with other European diplomats during the second European trip of Peter the Great. The diplomatic scandal of early 1717 connected to the disclosure of another Jacobite conspiracy involving the official circles of Sweden affected Areskin's endeavors. During these events, the doctor's secret negotiations with representatives of a state at war with Russia became public. Despite the official assurances of Peter the Great and Areskin about their non-involvement in the activities of the opponents of King George I of England, negotiations with the Jacobites continued later, during the tsar's stay in France and Holland. Areskin remained the main initiator of these contacts even after Peter I returned to Russia, which only aggravated the problematic relations with England. However, the death of the tsar's doctor led to the fact that the "Jacobite intrigue" in Russia was over.Medic G.Polikala was involved in the activities of Russian diplomacy in Turkey. In particular, he had contacts with the Russian envoy in Istanbul, P.A. Tolstoy, and attempted to withdraw A. Cantemir from the territory of the Ottoman Empire. Unfortunately, the information about Polikala's participation in Peter I's secret diplomacy events is sketchy.The article concludes that the tsarist doctors played an essential role in implementing the foreign policy initiatives of Peter I.